Anti-cancer effect of dihydrokaempferol in human malignant melanoma cell is mediated via inhibition of cell migration and invasion and up-regulation of NF-kB/MAPK signalling pathways (Bangladesh Journal of Pharmacology, 2016)
Article is withdrawn by the Authors